The life cycles of viscous decretion disks around Be stars: fundamental disk parameters in the SMC - Rímulo, Leandro Rocha (2017)
Be stars are main-sequence massive stars with emission features in their spectrum, which originates from a circumstellar gaseous disk. Even though the viscous decretion disk (VDD) model can satisfactorily explain most observations, two important physical ingredients, namely the magnitude of the viscosity (alpha) and the disk mass injection rate, remain poorly constrained. In addition, substantial work remains to be done in order to fully understand the life cycles of these disks: how fast they grow and dissipate, for how long they last, etc. The light curves of Be stars that undergo events of disk formation and dissipation offer an opportunity to study their life cycles and to constrain the disks fundamental properties. A pipeline was developed to model these events that uses a grid of synthetic light curves, computed from detailed hydrodynamic simulations combined with radiative transfer calculations. Comparison between model and data was made possible by two empirical laws we discovered, which closely match the photometric behaviour of the events. A sample of 54 Be stars from the OGLE survey of the Small Magellanic Cloud (SMC) was selected for this study. The typical mass and angular momentum loss rates associated with the disk events are of the order of 10E-10 solar masses per year and 5E36 g/(cm^2 s^2), respectively. We showed that the angular momentum lost by the star, even for the events with the densest disks, was still smaller than the required by the best evolutionary models so that the stars do not reach their break-up velocities. These numbers offer, for the first time, constraints on the internal angular momentum transport mechanisms of fast rotating massive stars. This work also increased the number of Be stars whose alpha parameters have been determined by 54 times, and it represents the first statistically significant determination of alpha for Be stars. The values of alpha found are typically of a few tenths, consistent with recent results in the literature and with the ones found in dwarf novae, but larger than the current theory predicts. Considering the sample as a whole, the viscosity parameter is roughly two times larger at build-up (alpha_bu = 0.63) than at dissipation (alpha_d = 0.29). Further work is necessary to verify whether this trend is real or a result of some of the model assumptions. If real, this is a phenomenon worth further investigation, as it may lead to clues as to the origin of anomalous viscosity in astrophysical disks. In the near future, we intend to extend our work to Be stars fromthe Large Magellanic Cloud (LMC) and from the Galaxy, by making use of the many photometric surveys, with years of coverage, available.